The study on toxicity of blended Jatropha biodiesel and mineral oil as based fluid in oil based mud - Han, Samantha Siang Eng, 1990-, author; Azmi Kamis, supervisor; Fakulti Kejuruteraan Petroleum dan Tenaga Diperbaharui (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2013